2018
DOI: 10.1371/journal.pone.0206114
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association of a common GNAS polymorphism with self-reported cognitive empathy in healthy volunteers

Abstract: BackgroundIn a recent study, we found associations of a common oxytocin receptor (OXTR) polymorphism with inter-individual differences in empathy, especially with emotional empathy in women. Many other studies found specific associations of oxytocin, arginine-vasopressin, serotonin and dopamine receptor gene polymorphisms with various aspects of trait empathy. As all these receptors belong to the guanine-binding protein (G protein) coupled receptor family, it is a reasonable assumption, that alterations in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…This study revealed that overweight patients exhibited higher levels of empathy compared to non-overweight patients. Although there is a paucity of literature on the empathic capacity of overweight patients, our finding is consistent with that of a previous study reporting that a metabolic-dysfunction-related gene was associated with higher cognitive empathy among female participants [47]. Moreover, another study found that among females with schizophrenia, those with higher BMI scores possessed a greater capacity for empathy [67].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study revealed that overweight patients exhibited higher levels of empathy compared to non-overweight patients. Although there is a paucity of literature on the empathic capacity of overweight patients, our finding is consistent with that of a previous study reporting that a metabolic-dysfunction-related gene was associated with higher cognitive empathy among female participants [47]. Moreover, another study found that among females with schizophrenia, those with higher BMI scores possessed a greater capacity for empathy [67].…”
Section: Discussionsupporting
confidence: 92%
“…Minoretti et al [78] hypothesized a possible association between the TT genotype and the schizophrenia deficiency syndrome subtype, for which affected patients typically present poor empathy [79]. However, C393C allele carriers have been shown to have more empathic tendencies, with higher IRI PT scores compared to C393T allele carriers, and the C393C allele has been recognized as a risk factor for several metabolic disorders, including obesity [47]. Third, our study observed a higher suicide rate in the overweight group, and related studies confirm that suicide relates to greater levels of empathy [80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is a possibility that an increase in physical activity enhances neuronal plasticity in the brain regions mentioned above 16,17) , it is assumed that physical activity in healthy young adults is related to self-reported cognitive empathy. Also, there is a possibility that the genotype of the G protein coupled receptor family, including the arginine-vasopressin receptor 1a, modulates cognitive empathy 18,19) , therefore, we should investigate whether the individual differences of genotype have an influence on the relationship of physical activity with cognitive empathy or not. Although physical activity was shown to be associated with cognitive empathy, this study showed that affective empathy remained unchanged with a usual level of physical activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin (5-hydroxytryptamine, 5-HT) is a neurotransmitter of complex multifaceted activity, produced in the CNS chiefly in the Raphe nuclei of the brainstem. Interestingly, multiple SNPs in the gene GNAS, encoding a G αs subunit that couples with serotonin receptors 5HT4 and 5HT7, the AVP receptor 2 and dopamine receptors of the D1-like family, have been identified in a screening of ASD patients [44][45][46][47]. Genetic association studies also linked ASD to the enzyme that catalyzes the conversion of tryptophan into 5-hydroxytryptophan (5-HTP) in the brain, tryptophan-hydroxylase 2 (TPH2) [48][49][50][51][52][53].…”
Section: Serotoninmentioning
confidence: 99%